2011
DOI: 10.1371/journal.pone.0022721
|View full text |Cite
|
Sign up to set email alerts
|

Carbenoxolone Blocks the Light-Evoked Rise in Intracellular Calcium in Isolated Melanopsin Ganglion Cell Photoreceptors

Abstract: BackgroundRetinal ganglion cells expressing the photopigment melanopsin are intrinsically photosensitive (ipRGCs). These ganglion cell photoreceptors send axons to several central targets involved in a variety of functions. Within the retina ipRGCs provide excitatory drive to dopaminergic amacrine cells via glutamatergic signals and ipRGCs are coupled to wide-field GABAergic amacrine cells via gap junctions. However, the extent to which ipRGCs are coupled to other retinal neurons in the ganglion cell layer via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…This conclusion became questionable when subsequent work showed that the percentage of light-responsive GCL neurons detected by Sekaran et al (~3%) roughly matched the percentage of ipRGCs [34], and that carbenoxolone could block the light-induced Ca 2+ dye responses of dissociated ipRGCs [35]. However, the demonstration of tracer coupling strengthened the possibility of ipRGC-amacrine coupling [10], which we validated here.…”
Section: Discussionsupporting
confidence: 58%
“…This conclusion became questionable when subsequent work showed that the percentage of light-responsive GCL neurons detected by Sekaran et al (~3%) roughly matched the percentage of ipRGCs [34], and that carbenoxolone could block the light-induced Ca 2+ dye responses of dissociated ipRGCs [35]. However, the demonstration of tracer coupling strengthened the possibility of ipRGC-amacrine coupling [10], which we validated here.…”
Section: Discussionsupporting
confidence: 58%
“…These channels may transmit, propagate and potentiate TRPV4 agonist‐initiated Ca 2+ signal through direct intercellular Cx channel or pannexin‐derived extracellular ATP . Furthermore, CBX has also been reported to block L‐type voltage‐gated Ca 2+ channels and prevent the light‐evoked increase in intracellular Ca 2+ in retinal ganglion cells and cultured rat cortical astroglia, respectively . Intriguingly, this channel has also reported to be implicated in diabetic bladder dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ -imaging recordings were baseline corrected, then the area-under-curve data of the records representing the net change in the intracellular free Ca 2+ -content were analyzed. Baseline correction was carried out by subtracting the background fluorescence measured from a region in the coverslip free of neurons [39]. …”
Section: Methodsmentioning
confidence: 99%